ANALISIS RESIKO TERHADAP KETERLAMBATAN PROYEK HOTEL BUMI SEGAH DI TANJUNG REDEB - Mawi, Tiarasari (STIE Muhammadiyah Tanjung Redeb, 2018)
AbstractThis study was conducted to determine the factors causing the retardation of the Bumi Segah hotel project with the highest risk ranking value. The analysis method in this study was Fishbone Diagram and the analysis of Mean Rank, the analysis results showed that the material variable is the highest ranking of the variable with the value of 3.26 on the rank 1. The material variable is considered as the most influential variable on the retardation of the completion of Bumi Segah hotel, where the indicator is viewed in terms of scarcity and distribution of materials that take too much time which causing the construction of the Bumi Segah hotel encounter retardation Keyword : Risk Analysis, Mean, Rank, The Couses of the Delay in the Project